Addressing chemical pollution in biodiversity research - Sigmund, Gabriel; Ågerstrand, Marlene; Antonelli, Alexandre; Backhaus, Thomas; Brodin, Tomas; Diamond, Miriam L; Erdelen, Walter R; Evers, David C; Hofmann, Thilo; Hueffer, Thorsten; Lai, Adelene; Torres, Joao P M; et al. (Global change biology, 2023)
Climate change, biodiversity loss, and chemical pollution are planetary-scale emergencies requiring urgent mitigation actions. As these "triple crises" are deeply interlinked, they need to be tackled in an integrative manner. However, while climate change and biodiversity are often studied together, chemical pollution as a global change factor contributing to worldwide biodiversity loss has received much less attention in biodiversity research so far. Here, we review evidence showing that the multifaceted effects of anthropogenic chemicals in the environment are posing a growing threat to biodiversity and ecosystems. Therefore, failure to account for pollution effects may significantly undermine the success of biodiversity protection efforts. We argue that progress in understanding and counteracting the negative impact of chemical pollution on biodiversity requires collective efforts of scientists from different disciplines, including but not limited to ecology, ecotoxicology, and environmental chemistry. Importantly, recent developments in these fields have now enabled comprehensive studies that could efficiently address the manifold interactions between chemicals and ecosystems. Based on their experience with intricate studies of biodiversity, ecologists are well equipped to embrace the additional challenge of chemical complexity through interdisciplinary collaborations. This offers a unique opportunity to jointly advance a seminal frontier in pollution ecology and facilitate the development of innovative solutions for environmental protection.
Keywords: klimatické změny; Environmental Pollution; ecology; ecotoxicology; combined stressor; ekologie; chemical pollution; biodiversity loss; Climate Change; biodiverzita; zachování přírodních zdrojů; Biodiversity; znečištění životního prostředí; Conservation of Natural Resources; Ecology; ekosystém; Ecosystem